2017
DOI: 10.1016/j.fuel.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and deformation changes in anthracite coal after methane adsorption

Abstract: Micropores are the primary sites of methane adsorption in coal, and the heterogeneous mesostructures of coal create the non-uniform distribution of the micropores in coal. Using a thermal infrared imager, the temperature distribution on the surface of an anthracite sample during methane adsorption/desorption was tested in this paper, and a new method is advanced to calculate methane adsorption capacity in coal based on its temperature increment. The results confirm the strongly non-uniform distribution of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 18 publications
4
34
0
Order By: Relevance
“… 26 At 507 and 1082 cm –1 , the peak of the smectite mineral was greatly reduced. Feng et al 4 found that mineral matters in coal samples preferentially adsorbed methane due to their smaller mesostructures than the coal matrix. The reduction of the clay minerals reduced the adsorption of methane, which was consistent with the adsorption test results in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 26 At 507 and 1082 cm –1 , the peak of the smectite mineral was greatly reduced. Feng et al 4 found that mineral matters in coal samples preferentially adsorbed methane due to their smaller mesostructures than the coal matrix. The reduction of the clay minerals reduced the adsorption of methane, which was consistent with the adsorption test results in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Gas adsorption leads to the deformation of the coal mesostructure including expansion and extrusion deformation. 61 The adsorption swelling stress and extrusion stress of the gas increase with the change in the coal sample damage. From Equation (32), it can be found that axial strain is the function of stress and time, and the effect of adsorption stress on the effective stress of coal can be offset under the triaxial compression.…”
Section: Three-dimensional Creep Equations For Coal Containing Gasmentioning
confidence: 99%
“…A large number of studies showed that the coal temperature is closely related to coal gas desorption. e higher the temperature, the larger the desorption rate [1][2][3][4][5][6][7][8][9][10][11]. Temperature changes during gas adsorption and desorption were tested using a gas outburst simulator [12,13].…”
Section: Introductionmentioning
confidence: 99%